2017
DOI: 10.1001/jama.2017.5427
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Oral Iron Repletion on Exercise Capacity in Patients With Heart Failure With Reduced Ejection Fraction and Iron Deficiency

Abstract: Importance Iron deficiency is present in approximately 50% of patients with heart failure with reduced left ventricular ejection fraction (HFrEF) and is an independent predictor of reduced functional capacity and mortality. However, the efficacy of inexpensive, readily available oral iron supplementation in heart failure is unknown. Objective To test whether therapy with oral iron improves peak exercise capacity in patients with HFrEF and iron deficiency. Design, Setting, and Participants Phase 2, double-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
324
0
34

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(359 citation statements)
references
References 34 publications
1
324
0
34
Order By: Relevance
“…Noteworthy, a sub-analysis of the seminal FAIR-HF trial [74] focusing on anemic CHF patients showed consistent Hb increase after IV iron, implicitly validating the above mentioned "extensive" criteria for ID [128]. As mentioned above, the beneficial effect of iron in CHF is seen only using IV preparation (for now FCM is the only compound tested in such condition), while a recent trial with oral iron was unsuccessful because of increased hepcidin levels [76]. As depicted in Fig.…”
Section: Expanding Spectrum Of Clinical Use Of IV Ironmentioning
confidence: 73%
See 2 more Smart Citations
“…Noteworthy, a sub-analysis of the seminal FAIR-HF trial [74] focusing on anemic CHF patients showed consistent Hb increase after IV iron, implicitly validating the above mentioned "extensive" criteria for ID [128]. As mentioned above, the beneficial effect of iron in CHF is seen only using IV preparation (for now FCM is the only compound tested in such condition), while a recent trial with oral iron was unsuccessful because of increased hepcidin levels [76]. As depicted in Fig.…”
Section: Expanding Spectrum Of Clinical Use Of IV Ironmentioning
confidence: 73%
“…This results in decreased utilization of O 2 by irondependent mitochondrial enzymes in cardiomyocytes [72], and an increased risk of hospitalization or even of death [70,73]. Of note, IV iron therapy has been shown to be beneficial in CHF patients with ID (see also below) [71,74,75], while a recent trial with oral iron yielded negative results [76]. This refractoriness to oral iron was linked to relatively high (instead of suppressed) hepcidin levels in CHF ID patients [76].…”
Section: Oral Iron Therapy In the Hepcidin Eramentioning
confidence: 99%
See 1 more Smart Citation
“…Ich rolą jest wyłapywanie i internalizacja transferryny w celu pozyskania żelaza przez komórki docelowe, podczas gdy rolą ferrytyny jest przechowywanie żelaza w tkankach (ryc. 3) [28,29].…”
Section: Następstwa Niedokrwistości I Niedoboru żElazaunclassified
“…При інфекційних процесах залізо гальмує фагоцитарну активність нейтро-філів і стимулює проліферацію мікробних аген-тів, хоча це застереження підтримують не всі дослідники. Більшість авторів надають перевагу застосуванню парентерального заліза в пацієнтів з АХЗ [26,30].…”
unclassified